(untitled) (Cardiovascular Journal, 2015)
Background: The association between extent and severity of coronary artery disease (CAD) and renal artery stenosis (RAS) has been well established in many studies. The aim of this study was to assess the incidence and severity of RAS in patients with CAD. Methods: Coronary angiogram (CAG) and renal angiogram was done in standard protocol. A total of 95 patients was included in the study and divided into two groups according to the presence of significant renal artery stenosis. In Group I 45 patients were having normal or insignificant renal artery stenosis. In Group II 50 patients were having significant renal artery stenosis. All data were recorded systematically in preformed data collection form. Results: In Group I, most common CAG findings were single vessel disease (SVD) (91.1%), triple vessel disease (TVD) (2.2%) and double vessel disease (DVD) (6.7%). No patients in Group I had Left Main (LM) disease. In Group II, most common CAG findings were DVD (42.0%) followed by SVD 32.0%, TVD 26.0% and LM 8.0%. There is statistically significant difference in Vessels Score, Friesinger Score and Leaman Score between the groups (p<0.05). Conclusion: The study revealed significant association between atherosclerotic renal artery stenosis (RAS) and severity of coronary artery disease (CAD). This indicates significant atherosclerotic renal artery stenosis (RAS) predict the severity of coronary artery disease. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22258 Cardiovasc. j. 2015; 7(2): 114-118